Asia-Pacific economic cooperation the goods market - Paderanga, Cayetano W., Jr. (1995)
This article looks into the static and dynamic effects of free trade areas such as the ASEAN Free Trade Area (AFTA) and the Asia-Pacific Economic Cooperation (APEC). It emphasizes the political economic role by these groupings in a step-by-step process of opening up and liberalization. It also examines some of the costs of joining APEC and what may be done to ease the process of adjustment.
Keywords: Free trade -- Southeast Asia; Asia-Pacific Economic Cooperation (Organization)